Removal and Recovery of Phosphate from Water and Wastewater Using Metal-Loaded Agricultural Waste-Based Adsorbents: A Review - Pokhrel, Megh Raj; Poudel, Bhoj Raj; Aryal, Ram Lochan; Paudyal, Hari; Ghimire, Kedar Nath (Journal of Institute of Science and Technology, 2019)
There is a growing research interest in the development of adsorbents based on agricultural wastes (AWs) for the removal of phosphate from waste water sources, which otherwise can cause eutrophication. Nevertheless, due to the lack of active exposed surface sites, raw AWs-based adsorbents are usually inefficient for the adsorption of phosphate from aquatic environment. Consequently, modification of raw adsorbents has been frequently used to improve their phosphate adsorption capacity. Of the various methods of modification, this review paper focused on most widely used chemical modification method. It presents a critical and comprehensive review of the literature on the effectiveness of metal-loaded agricultural wastes (MLAWs)-based adsorbents in removing and recovering of phosphate from waste waters. Mechanisms and factors affecting phosphate adsorption as well as phosphate desorption and regeneration from MLAW adsorbents are critically evaluates. If phosphate from waste waters can be of economical value, regeneration may partly overcome the future shortage of global phosphate rock reserves. It is evident from the literature survey presented herein that MLAWs-based adsorbents exhibited as potential adsorbent for the removal/recovery of phosphate from waste waters. However, there still needs a refined practical utility of these adsorbents on a commercial scale, which may serve as the novel, cost effective and environmentally benign methods of modification.